Dieux et lieux de la Méditerranée antique : des outils numériques pour l’histoire des religions - Élodie Guillon; Antoine Laurent (Humanités Numériques)
This article presents several digital tools used in the ERC MAP project (Mapping Ancient Polytheisms), which deals with the history of religions in the ancient Mediterranean. The project uses database management systems (DBMS), webmapping and formalization tools, in order to deal with substantial but heterogeneous documentation, with a chrono-geographical scope unique in the field. The article focuses on the choices and stages of implementation of tools that respect the FAIR data principles. It provides a concrete example highlighting a multidisciplinary scientific project at the crossroads of history and digital practices.